Gender and disease severity determine proximal femoral morphology in developmental dysplasia of the hip. Issue 5 (28th March 2019) - Boughton, Oliver R.; Uemura, Keisuke; Tamura, Kazunori; Takao, Masaki; Hamada, Hidetoshi; Cobb, Justin P.; Sugano, Nobuhiko
ABSTRACT: In this computed tomography (CT) morphological study we describe the way the proximal femoral morphology differs with worsening degrees of developmental dysplasia of the hip (DDH) and describe gender differences in patients with DDH. Forty‐nine male patients with DDH were matched with 49 females with DDH, using age and the Crowe classification of DDH severity. The femoral length, anteversion, neck‐shaft angle, offset, neck length, canal‐calcar ratio, canal flare index, lateral center‐edge angle, alpha angle, pelvic tilt, and pelvic incidence were measured for each patient on their pre‐operative CT scans, prior to total hip arthroplasty surgery. Femoral anteversion and neck length were 16° and 47 mm, 25°and 36 mm, 26° and 43 mm, and 44° and 36 mm, for Crowe I and III males and Crowe I and III females, respectively. The mean male anteversion was 22° (±14), compared to 30° (±15.5) in females ( p  = 0.02, Confidence Interval: 1.6–14.9). Gender differences in femoral length, neck length and offset lost significance when height‐normalized and no other significant gender differences were found. In conclusion, femoral neck length reduces with increasing DDH severity, whilst anteversion tends to increase. Male patients with DDH have significantly less femoral anteversion, which has important implications for osteotomy and arthroplasty surgery in DDH. © 2019 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res